Foliar nutrient resorption in rubber trees (Hevea brasiliensis) - Jessy, M.D.; Joseph, Phebe (Journal of Plantation Crops, 2012)
The extent of resorption of nutrients before senescence was determined in a rubber plantation which received nutrients at different ratios from establishment onwards. Rubber tree is a leaf exchanging species which defoliates before the onset of dry season, and refoliates within 2-3 weeks, during the middle of dry season. The objective of the study was to quantify the extent of resorption of major nutrients and the influence of nutrient supply on nutrient resorption. Substantial part of the nutrients was resorbed before leaf fall, 52 to 66 percent N, 53 to 80 percent P and 48 to 88 percent K were resorbed depending on the rate of fertilizer application. Year to year variation in nutrient resorption was observed. Resorption proficiency and efficiency of K were significantly influenced by nutrient ratios, wider N:K ratios resulting in significantly higher resorption proficiency and efficiency. The study concludes that nutrient resorption is an important nutrient conservation mechanism of rubber trees and change in soil nutrient dynamics will influence the extent of resorption and thus litter quality.